solve the equation using substitution

y = 3x + 7
y= -4x

1 answer

Since both expressions are equal to y, we can set them equal to each other and solve for x:

3x + 7 = -4x

Adding 4x to both sides:
7x + 7 = 0

Subtracting 7 from both sides:
7x = -7

Dividing by 7:
x = -1

Now that we have x, we can substitute it back into either equation to solve for y. Let's substitute it into the second equation:

y = -4(-1)
y = 4

Therefore, the solution to the system of equations is x = -1 and y = 4.
Similar Questions
  1. Solve the system of equations by SUBSTITUTION.6y+5x=8 x+3y=−7 (1 point) ​What would your equation look like after the first
    1. answers icon 1 answer
  2. Use the Substitution method to solve the system of equations.x + y = -4 x - y = 2 solve for x in the second equation. x= y+2 Put
    1. answers icon 5 answers
    1. answers icon 30 answers
    1. answers icon 1 answer
more similar questions